Verification of reference genes for relative quantification of gene expression by real-time reverse transcription PCR in the pig - Svobodová, Katerina; Bílek, Karel; Knoll, Ales (Journal of applied genetics, 2008)
The aim of this study was to develop a set of reliable reference genes for quantification of mRNA expression in the pig. The mRNA expression stability in pig tissues was studied for 4 genes: EEF1A1, GAPDH, HPRT1 and TOP2B. The level of expression was characterized by Ct values for each gene and each tissue. By using the geNorm algorithm, the stability of the reference genes was determined in the diaphragm, heart, kidney, liver, lungs, longissimus muscle, and spleen. On the basis of this information, suitable reference genes can be selected for mRNA expression studies in relevant pig tissues.
Keywords: prasata; tkáňová distribuce; exprese genu; Swine; Gene Expression; RNA, Messenger; DNA-topoisomerasy typu II; DNA-Binding Proteins; glyceraldehyd-3-fosfátdehydrogenasa (NADP+); Tissue Distribution; elongační faktor 1; DNA Topoisomerases, Type II; DNA vazebné proteiny; polymerázová řetězová reakce s reverzní transkripcí; referenční standardy; Peptide Elongation Factor 1; Animals; Glyceraldehyde 3-Phosphate Dehydrogenase (NADP+); zvířata; Reverse Transcriptase Polymerase Chain Reaction; Reference Standards; Hypoxanthine Phosphoribosyltransferase; messenger RNA; hypoxanthinfosforibosyltransferasa